Isatin-based Strategies for Microbial Infections: A Multifaceted Perspective - Radhika Sharma; Manjot Singh; Pushp Kashyap; Shubhangi Mishra; Kalpana Rahate (Reviews on Recent Clinical Trials, 2026)
Abstract: Novel chemotherapeutic drugs that can fight multidrug-resistant bacteria are desperately needed due to the fast growth of antimicrobial resistance (AMR). As a favoured scaffold in medicinal chemistry, the naturally produced indole derivative isatin (1H-indole-2,3-dione) is found in microorganisms, plants, and the metabolic pathways of mammals, has garnered significant interest. Isatin is a crucial pharmacophore for the creation of broad-spectrum antibacterial medicines because of its adaptable chemical structure and ease of structural alteration at several reactive locations. The therapeutic potential of isatin and its derivatives against bacterial, fungal, viral, and microbacterial diseases is well highlighted in this study. Schiff bases, Mannich bases, thiosemicarbazones, azole, furan, sulfonamide, fluoroquinolone, chalcone, and coumarin conjugates are among the many isatinbased hybrids and analogs that show strong and specific antimicrobial action. According to mechanistic investigations, these compounds function via a variety of mechanisms, including biofilm suppression, membrane disruption, interference with DNA gyrase and topoisomerase IV, inhibition of cell-wall production, and targeting vital enzymes like FtsZ and CrtM. To enhance biological potency and overcome drug resistance, electronic substituents, linker flexibility, and hybridization techniques are crucial, according to structure–activity relationship (SAR) studies. The clinical approval of numerous isatin-based drugs, including sunitinib and nintedanib, for the treatment of cancer, as well as the evaluation of other drugs, like TD-1792 and Ro 23-9424, for the treatment of infectious diseases, demonstrate the translational success of this scaffold. This review focuses on significant advancements, procedures, and potential treatments in isatin-based antimicrobial research.